Comparative analysis of sequentiality using SDIS-GSEQ and THEME: A concrete example in soccer - Lapresa, D.; Arana, J.; Anguera, M. T.; Garzón, B. (Journal of Sports Sciences, 2013)
Within an observational design aimed at studying what type of soccer is better adapted to the possibilities of the 11-12 year-old child, a comparison was made of the results obtained using two fully consolidated analysis techniques in observational methods, and which form the basis in the development of two respective software programs: SDIS-GSEQ and THEME, which allow one to detect the existence of sequential patterns hidden in a data set. This work is intended to shed light on the comparison of results obtained using these two analysis techniques. In particular, the data used for the analysis are multicode event data (using the lexicon of the sequential analysis), and do not incorporate the duration parameter. Accordingly, for the detection of regular structures using the THEME program (T-patterns), a constant duration has conventionally been assigned to each occurrence. Using THEME, among the greatest number of sequential structures detected, diachronic and synchronic correspondence was observed (T-patterns reflecting identical multi-events) with each and every one of the sequential patterns obtained using the lag technique, by the SDIS-GSEQ software. This coincidence strengthens the link between the algorithms that support SDIS-GSEQ and THEME. The results indicate that 7-a-side soccer and 9-a-side soccer types facilitate the spatial mastery of the game by the child, compared with the adult form, 11-a-side soccer.